1985
DOI: 10.1161/01.hyp.7.4.547
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of vasopressin and angiotensin to the maintenance of blood pressure after autonomic blockade.

Abstract: SUMMARY The contribution of vasopressin and angiotensin II to the maintenance of blood pressure after short-term autonomic blockade was investigated in conscious Long-Evans and Brattleboro (vasoprcssin-deficient; hereditary diabetes insipidus) rats. After short-term autonomic blockade by atropine (1 mg/kg), propranolol (5 mg/kg), and pentolinium (5 mg/kg and 10 mg/kg/hr), the fall in blood pressure was significantly greater in Brattleboro rats than in Long-Evans rats (48 ± 3 vs 32 ± 2 mm Hg; p < 0.01). Adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…It is known that the activity of the renin-angiotensin system is enhanced in DI rats, possibly as a means of compensating for the absence of AVP. 24 However, under the same experimental conditions as applied in the present study, Hiwatari et al 23 demonstrated that, after total autonomic blockade, blood pressure in DI rats was lower than that in LE rats, and the reninangiotensin system was activated more by autonomic blockade in the former. Therefore, higher blood pressure in DI rats may not be attributable to enhanced activity of the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…It is known that the activity of the renin-angiotensin system is enhanced in DI rats, possibly as a means of compensating for the absence of AVP. 24 However, under the same experimental conditions as applied in the present study, Hiwatari et al 23 demonstrated that, after total autonomic blockade, blood pressure in DI rats was lower than that in LE rats, and the reninangiotensin system was activated more by autonomic blockade in the former. Therefore, higher blood pressure in DI rats may not be attributable to enhanced activity of the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 43%
“…21 When one system is removed, its influence can be partially and sometimes completely compensated by increased activity in the remaining systems. 22 ' 23 Thus, the deficiency of circulating AVP in DI rats may not necessarily result in hypotension, but the relatively higher blood pressure levels observed in DI rats are not easily explained. Several possible mechanisms may be postulated.…”
Section: Discussionmentioning
confidence: 99%
“…Hiwatari et al 23 recently showed that immediately after pentolinium-induced autonomic block there was transient release of angiotensin II and vasopressin, which helped to maintain blood pressure. However, we believe that circulating hormones played only a small role in accounting for the response differences between hypertensive and normal rabbits, since (1) the elevations of hormone concentrations demonstrated by Hiwatari et al 23 were only transient and would be small 20 minutes after giving blocking drugs when we obtained our first doseresponse curve; (2) the differences in dose-vascular response curves between hypertensive and normal rabbits were similar with all drugs, some of which would produce differential changes in hormone concentrations; (3) there was no time-dependence on resting blood pressure and vascular resistance over the entire time course of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Baroreceptors, present in the adventitia of conduit vessels such as the aorta and carotid arteries, may reset as a consequence of alterations in vessel distensibility (Koushanpour, 1991). GTN is known to increase arterial compliance (Sumimoto et al, 1993) (Hiwatari et al, 1985). Further studies are required to examine the involvement of these neurohumoral effectors in modulating the dose dependence of the depressor action of GTN.…”
Section: Rabbit Body Weightmentioning
confidence: 99%